Cashew apple juice containing gluco-oligosaccharides, dextran, and tagatose promotes probiotic microbial growth. (August 2021) - Leite, Ana K.F.; Santos, Brenda N.; Fonteles, Thatyane V.; Rodrigues, Sueli
Abstract: The gut microbiota plays an essential role in host health. The ingestion of prebiotic foods can improve the balance and composition of this microbiota. In the present study, the prebiotic cashew apple juice was produced by enzyme synthesis using its sugars as substrate. The oligosaccharides synthesis was carried out with and without agitation by dextransucrase enzyme (30 °C/17 h). Tagatose restored the juice sweetness. An in vitro digestion was carried out at 37 °C/6 h to evaluate the functional juice samples' prebiotic effect on the probiotic strain Lactobacillus casei NRRL B-442, Bifidobacterium breve NRRL B-41408, and Bifidobacterium infantis NRRL B-41661 growth. Oligosaccharides, dextran, and tagatose were resistant to gastrointestinal conditions and stimulated the probiotic strains' growth. However, each microorganism had a different behavior and preferably consumed some carbohydrates. Tagatose proved to be a suitable substrate for the growth of Bifidobacterium infantis NRRL B-41661 with a maximum consumption rate of 0.045 h −1 . On the other hand, Lactobacillus casei NRRL B-442 and Bifidobacterium breve NRRL B-41408 showed maximum growth rates associated with high consumption rates of dextran and oligosaccharides. This study pointed out an excellent alternative for consumers and the functional food market. When metabolized by beneficial microorganisms, the prebiotic juice in the gut promoted these probiotics' growth. Graphical abstract: Image 1